Influenza A virus hemagglutinin glycosylation compensates for antibody escape fitness costs. - Ivan Kosik; William L Ince; Lauren E Gentles; Andrew J Oler; Martina Kosikova; Matthew Angel; Javier G Magadán; Hang Xie; Christopher B Brooke; Jonathan W Yewdell (PLoS Pathogens, 2018)
Rapid antigenic evolution enables the persistence of seasonal influenza A and B viruses in human populations despite widespread herd immunity. Understanding viral mechanisms that enable antigenic evolution is critical for designing durable vaccines and therapeutics. Here, we utilize the primerID method of error-correcting viral population sequencing to reveal an unexpected role for hemagglutinin (HA) glycosylation in compensating for fitness defects resulting from escape from anti-HA neutralizing antibodies. Antibody-free propagation following antigenic escape rapidly selected viruses with mutations that modulated receptor binding avidity through the addition of N-linked glycans to the HA globular domain. These findings expand our understanding of the viral mechanisms that maintain fitness during antigenic evolution to include glycan addition, and highlight the immense power of high-definition virus population sequencing to reveal novel viral adaptive mechanisms.